“It’s Like we Have Our Own Rhythm”. Music Therapeutic Affect Regulation in a Case Study of a Traumatized Patient in Mental Health Treatment - Bjørke, Oda Dypvik; Beck, Bolette Daniels (Voices: A World Forum for Music Therapy, 2023)
This article explores how music therapy can contribute to the treatment of individuals with affect regulation challenges related to relational traumatic experiences. Affect regulation was investigated through a case study of music therapy with a man with complex post-traumatic stress disorder. The case represents clinical work in a psychiatric hospital, on a ward for ambulatory treatment of people with severe mental illness and substance abuse challenges. Based on theories of communicative musicality, intersubjectivity and traumatology, an analysis of transcripts of music therapy improvisations and verbal interaction is presented and discussed. The method used in the study is an abductive explanatory thematic analysis grounded in hermeneutic interpretation of data. The two main themes emerging from the analysis are “Musical interaction as co-regulation” and “Music as a creative (re)source” with the subthemes “Musical interventions serves as a regulation tool”, “A process from regulation to relationship, “Musical self-agency” and “Music therapy as an experimental playground”. Further studies on affect regulation in clinical music therapy are warranted.